IoT applications, security threats, and countermeasures - Nayak, Padmalaya; Ray, Niranjan K., 1974-; Ravichandran, P. (Educator) (Boca Raton : CRC Press, 2022)
"The book explores modern sensor technologies while also discussing security issues, which is the dominant factor for many types of Internet of Things (IoT) applications. It also covers recent (IoT) applications such as the Markovian Arrival Process, fog computing, real-time solar energy monitoring, healthcare, and agriculture. Fundamental concepts of gathering, processing, and analyzing different Artificial Intelligence (AI) models in IoT applications are covered along with recent detection mechanisms for different types of attacks for effective network communication. On par with the standards laid out by international organizations in related fields, the book focuses on both core concepts of IoT along with major application areas. Designed for technical developers, academicians, data scientists, industrial researchers, professionals, and students, this book is useful in uncovering the latest innovations in the field of IoT"--
IoT : the technological fad of the digital age / Corinne Jacqueline Perera, Shangrao University, China -- Significance of smart sensors for IoT applications / Vinay Kumar Awaar, Praveen Jugge, Padmalaya Nayak -- Applications of the batch Markovian arrival process in IoT / Srinivas R. Chakravarthy.
OCLC-licensed vendor bibliographic record.
Keywords: Internet of things -- Security measures; COMPUTERS / Information Technology; COMPUTERS / Networking / Security; COMPUTERS / Cryptography